Morphometric and ultrastructural analysis of the effect of bromocriptine and cyclosporine on the vasospastic femoral artery of rats - Tokmak, Mehmet; Başocak, Kahan; Canaz, Hüseyin; Canaz, Gökhan; İplikçioğlu, Celal (E-Century Publishing Corporation, 2015)
Vasospasm is the main causes of mortality and morbidity in patiens with subarachnoid hemorrhage (SAH). The arterial narrowing mechanism that develops after SAH is not yet fully understood but many studies showed that hypotension, neurogenic reflexes, clots in the subarachnoidal space, spasmogenic agents, humoral and celluler immunity play a role in the etiology. In this study we investigate the effects of Bromocriptine and Cyclosporine A in vasospasm secondary to SAH on rat femoral artery from ultrastructural and morphometric perspectives. 120 male Sprague-Dawley rats divided into 12 groups: Vasospasm (V), control (K), surgical control (CK) groups, vasospasm+Bromocriptine and/or Cyclosporine-A groups (VCyA, VBr, VBr+CyA), Bromocriptine and/or Cyclosporine-A control groups (CK, BK, Br+CyAK), Bromocriptine and/or Cyclosporine-A surgical control groups (BCK, CyCK, Br+CyACK). In order to create SAH model, 0, 1 cm(3) blood injected into silastic sheath wrapped rat femoral artery. Bromocriptine (2 mg/kg/d) and Cyclosporine A (10 mg/kg/d) combinations applied to control, surgical control and vasospastic models. Light microscopy, transmission electron microscopy and scanning electron microscopy used during this study. Statistical evaluation of the morphometric measurement data concerning vascular wall thickness and luminal cross-sectional areas of all groups were performed using Mann-Whitney U, Wilcoxon-signed rank, and Student-t tests. Cyclosporine A, whose effects in the prevention of vasospasm have been demonstrated in previous studies. In this study we discovered that Bromocriptine demonstrated strong effects similar to Cyclosporine-A. Bromocriptine and Cyclosporine A markedly prevent the development of chronic morphologic vasospasm following SAH. The combined use of both drugs does not change this preventive effect.
WOS: 000367669800019
PubMed ID: 26770311
Keywords: Bromocriptine; Cyclosporine-a; Subarachnoid Hemorrhage; Vasospasm